(untitled) (Journal of the College of Basic Education, 2026)
The present study aims to identify the effectiveness of an educational program based on participatory art in developing cooperation and communication skills among second-grade intermediate students. The importance of the study stems from the need to develop social skills at this educational stage due to their role in enhancing positive interaction and teamwork within the school environment, particularly in art education classes. The researcher adopted the experimental method using a pre-test and post-test design with an experimental group and a control group. The research sample consisted of 50 students from the second intermediate grade at Al-Duha Intermediate School for Girls, affiliated with the Directorate of Education of Baghdad / Al-Karkh First, and was equally divided into two groups. The experimental group was taught using the participatory art-based program, while the control group was taught using the traditional method. Two observation checklists were used to measure cooperation and communication skills. The results revealed statistically significant differences in favor of the experimental group, confirming the effectiveness of the program in developing the targeted skills.